Prasasti Padang Candi: Tinjauan Epigrafis Temuan Data Tertulis dari Situs Padang Candi, Kabupaten Kuantan Singingi, Provinsi Riau - Ery Soedewo (Berkala Arkeologi Sangkhakala, 2013)
AbstractPadang temple inscription is one of the few written records of the ancient Indian culture in Indonesia. The written record unfortunately still fails to provide a data of the period and background. This paper uses an inductive reasoning that comprises such processes of data collection, detailing, analysis, interpretation, and conclusion. This gold plate inscription containing the Buddha formula ye te mantra may relatively be from between the 9th and 10th centuries A.D. The content of the inscription suggests that the Padang temple site may be the remains of a Buddha temple complex.AbstrakPrasasti Padang Candi adalah salah satu data tertulis dari masa pengaruh kebudayaan India di Nusantara yang tidak banyak jumlahnya. Prasasti yang ditulis di atas lembaran emas ini secara relatif berasal dari abad ke-9 hingga ke-10 M, yang memuat mantra Buddha formula ye te mantra. Berdasarkan muatan prasasti ini, sisa-sisa bangunan bata di Situs Padang Candi diperkirakan adalah sisa-sisa kompleks suatu percandian yang berlatar belakang agama Buddha.